2011
DOI: 10.1016/j.neuroscience.2010.10.070
|View full text |Cite
|
Sign up to set email alerts
|

Chronic stress alters neural activity in medial prefrontal cortex during retrieval of extinction

Abstract: Chronic restraint stress produces morphological changes in medial prefrontal cortex and disrupts a prefrontally mediated behavior, retrieval of extinction. To assess potential physiological correlates of these alterations, we compared neural activity in infralimbic and prelimbic cortex of unstressed versus stressed rats during fear conditioning and extinction. After implantation of microwire bundles into infralimbic or prelimbic cortex, rats were either unstressed or stressed via placement in a plastic restrai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
93
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(101 citation statements)
references
References 56 publications
(108 reference statements)
6
93
2
Order By: Relevance
“…In vivo recordings have demonstrated that activity within the PL cortex, the region of the mPFC where we studied LTD, is correlated with freezing behavior during fear extinction (32,(38)(39)(40). During states of high fear and freezing, neurons within the PL will display robust firing in response to fear cues, such as a tone CS.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo recordings have demonstrated that activity within the PL cortex, the region of the mPFC where we studied LTD, is correlated with freezing behavior during fear extinction (32,(38)(39)(40). During states of high fear and freezing, neurons within the PL will display robust firing in response to fear cues, such as a tone CS.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to other kinds of stressors also induces deficits in extinction retention. These include brief uncontrollable stress (Izquierdo et al 2006), chronic stress (Miracle et al 2006;Garcia et al 2008;Baran et al 2009;Wilber et al 2011), and footshock stress (Rau et al 2005;Maren and Chang 2006). Also, animals that are vulnerable to the effects of stress show extinction retention deficits (Goswami et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Exposing animals to brief uncontrollable and chronic stress prior to fear conditioning, or conducting fear conditioning in animals that are vulnerable to stress, enhances cued conditioned responding during fear conditioning and/or fear extinction (Izquierdo et al 2006;Miracle et al 2006;Goswami et al 2010;Wilber et al 2011), which suggests that stress-induced changes in fear memory may contribute to changes in extinction retention. This interpretation is also supported by the observation that, when the cue and the footshock presentations are not explicitly paired during fear conditioning (i.e., pseudoconditioning), chronic stress pre-exposure has no effect on extinction retention (Baran et al 2009;Wilber et al 2011). SPS exposure prior to fear conditioning disrupted extinction retention without having any effects on acquisition or expression of conditioned fear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations